2017
DOI: 10.1186/s41100-017-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between B-lines detected during lung ultrasound and various factors in hemodialysis patients

Abstract: Background: In recent years, the use of chest ultrasonography to detect lung water has received growing attention in clinical research. Estimation of the number of B-lines using lung ultrasound is now a standard method for the evaluation of pulmonary congestion. In the present study, we examined the relation between the number of B-lines and clinical parameters in hemodialysis patients. Methods: A total of 49 consecutive patients receiving maintenance hemodialysis were enrolled in this study. Lung ultrasound w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The lateral zone was positioned from the anterior axillary line to the posterior axillary line and was also divided into the upper and lower halves. The investigator attempted to detect comet tail artifacts fanning out from the lung-wall interface and spreading to the edge of the screen, which were previously named B-lines [5,8]. The total number of B-lines was estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral zone was positioned from the anterior axillary line to the posterior axillary line and was also divided into the upper and lower halves. The investigator attempted to detect comet tail artifacts fanning out from the lung-wall interface and spreading to the edge of the screen, which were previously named B-lines [5,8]. The total number of B-lines was estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The number of post-dialysis Blines is correlated with the residual weight assessed using bioimpedance, suggesting a role for ultrasound in the management of hemodialysis patients [7]. Lung ultrasound is also reportedly useful for the accurate evaluation of dry weight and fluid status in hemodialysis patients [2,8,9]. The number of B-lines observed using lung ultrasound represents the severity of pulmonary congestion [10].…”
Section: Introductionmentioning
confidence: 99%
“…B-lines within physiological range may be present. We have previously reported that B-lines are associated with low serum level of albumin and low body weight [6]. So, optimal number of B-lines may be different among hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators attempted to detect comet tail artifacts fanning out from the lung-wall interface and spreading to the edge of the screen, which were previously named as B-lines ( Fig. 1) [5,6]. The total number of B-lines was estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation